2020
DOI: 10.3390/jcm9051550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Lymphatic Filariasis Infection and Its Morbidity Following Mass Ivermectin and Albendazole Administration in Mkinga District, North-Eastern Tanzania

Abstract: Lymphatic filariasis (LF) is a neglected tropical disease targeted for elimination as public health problem through morbidity management and preventive annual mass drug administration (MDA). This cross-sectional community-based surveillance assessed the prevalence and correlates of LF infection in Mkinga district, Tanga-region, Tanzania. A total of 4115 individuals (49.7% males, 35.2% children) were screened for circulating filarial antigens (CFA), microfilaremia (mf) and disease manifestations in 15 villages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
(54 reference statements)
1
10
0
1
Order By: Relevance
“…The prevalence of Mf was below the WHO-recommended elimination threshold of 1%; however, the prevalence of antigenemia remains above the recommended threshold of 2% [ 6 ], indicating that the district is yet to interrupt LF transmission. The prevalence of CFA and Mf reported in the current study are corroborated by the findings from a recent study in Mkinga District, North-eastern Tanzania [ 26 ] reporting a CFA and Mf prevalence of 5.8% and 0.3% respectively. Similarly, a significant drop in microfilaraemia was reported in Zanzibar after five rounds of MDA with ivermectin and albendazole complemented with intensive community mobilization and high treatment coverage [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of Mf was below the WHO-recommended elimination threshold of 1%; however, the prevalence of antigenemia remains above the recommended threshold of 2% [ 6 ], indicating that the district is yet to interrupt LF transmission. The prevalence of CFA and Mf reported in the current study are corroborated by the findings from a recent study in Mkinga District, North-eastern Tanzania [ 26 ] reporting a CFA and Mf prevalence of 5.8% and 0.3% respectively. Similarly, a significant drop in microfilaraemia was reported in Zanzibar after five rounds of MDA with ivermectin and albendazole complemented with intensive community mobilization and high treatment coverage [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, the high incidence of AEs in the 16–20 years of age category may not be explained by variation in metabolic drug capacity. A recent study reported a high prevalence of LF infection in young adults and the elderly (65+ years) [ 31 ]. Previous studies reported significant side-effects often associated with the treatment of LF in infected patients due to treatment-induced immunologic reaction [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that the WHO intervention strategy and implementation of the global NTD program have contributed to reducing the disease burden. However, the long-term intervention measures taken so far by many endemic countries in sub-Saharan Africa, including Rwanda, have not managed to control and eliminate STH and other NTDs as a public health problem by 2020 [ 16 , 20 , 30 , 31 ]. Several factors may have contributed to this shortcoming [ 32 ].…”
Section: Discussionmentioning
confidence: 99%